Historisitas Kisah Fir'aun Dalam Perspektif Islam - Effendi, Effendi (AL-ADYAN, 2018)
The focus of this article is to reveal the description of Pharaoh expressed in the texts of the Qur'an. The research approach used is the historical approach of Fazlur Rahman. Based on the results of the study, conclusions were found as follows: First, Pharaoh according to the Koran is the rulers who in carrying out their government use an oppressive system, this oppression is supported by its authorities. Second, the mission carried out by Moses was the Liberation of the Children of Israel from the shackles of oppression and slavery. The Children of Israel as Mustadl'afin in the story need to be addressed in the present context, because the term Mustadl’afin is not only found in the Pharaoh period but always exists in every level of society, so concrete steps are needed to release from the oppressors' grip. Third, the Story of Pharaoh cannot be understood as we read texts in history, because in it there are many moral ideas that must be raised amid the collapse of oppressive systems.